Regioselective Aromatic Nucleophilic Substitution in N-Aryl-2-nitrosoanilines with Oxygen and Nitrogen Nucleophiles - Wróbel, Zbigniew; Stachowska, Karolina; Kwast, Andrzej (Synthesis, 2013)
Aromatic nucleophilic substitution of halogens in N-aryl-2-nitrosoanilines with ammonia, alkylamines and alkoxide ions proceeds efficiently and highly regioselectively in the position para to the nitroso group. When two halogen atoms ortho and para are present, the latter is substituted exclusively. Oxidative substitution of hydrogen at the unsubstituted ortho position of the nitrosoaniline ring does not compete with substitution of para halogen atoms. The reaction allows the synthesis of N-aryl-2-nitrosoanilines which cannot be obtained according to known methods.
Keywords: arenes; amines; nucleophilic aromatic substitution; regioselectivity; nitroso group